Biomasa y stock de carbono almacenado en las especies comerciales del bosque de colina baja de la pc 03 de la concesión forestal N° 16-LOR-MAY/CON-MAD-2017-024, distrito de Mazán, Loreto. 2021 - Bustios Ventura, Bernard (2022)
The biomass and the carbon stored in the commercial species of a low-hill forest of the Mazán district, Loreto, Peru were quantified. The data from the forest census of the commercial species of the operational plan (OP) 1 of the cutting plot (PC) 6 of the forest concession contract for timber purposes was evaluated. The results indicate a biomass of 2379,28 kg/ha and 2 092 812,87 kg, where V. calophylla reports the highest amount of biomass of 1096,96 kg/ha and 964 884,26 kg and the lowest value shows C. odorata with 18,09 kg/ha and 15 911,57 kg. The carbon stored amounts to 1,19 tC/ha and 1046.41 tC, where V. calophylla (0,55 tC/ha and 482,44 tC) reports the highest value; whereas C. odorata (0,01 tC/ha and 7,96 tC) shows the lowest value. The diameter classes from 60 cm to 69 cm (0,299 tC/ha) and from 50 cm to 59 cm (0,241 tC/ha) contain the highest amount of carbon stored and the diameter classes from 90 cm to 99 cm (0,062 tC/ha) and from 100 cm to 109 cm (0,080 tC/ha) show lower values of stored carbon.